2020
DOI: 10.1002/cne.24997
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the speech‐ready brain: The voice/jaw connection in the human motor cortex

Abstract: A prominent model of the origins of speech, known as the “frame/content” theory, posits that oscillatory lowering and raising of the jaw provided an evolutionary scaffold for the development of syllable structure in speech. Because such oscillations are nonvocal in most nonhuman primates, the evolution of speech required the addition of vocalization onto this scaffold in order to turn such jaw oscillations into vocalized syllables. In the present functional MRI study, we demonstrate overlapping somatotopic rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 57 publications
1
31
0
1
Order By: Relevance
“…A final point of discussion regarding left dPM is the issue of hemispheric laterality. In terms of speech production, it is well established that dLMC is represented bilaterally (Simonyan, 2014), and it has been further suggested that, if anything, activation during phonation is right dominant in the gyral dLMC (Brown et al, 2020). In the present study, significant STRF tuning was observed only in the left dPM.…”
Section: Left Dpm: Encoding Of Vocal Pitch In the Dorsal Laryngeal Motor Cortexsupporting
confidence: 54%
See 1 more Smart Citation
“…A final point of discussion regarding left dPM is the issue of hemispheric laterality. In terms of speech production, it is well established that dLMC is represented bilaterally (Simonyan, 2014), and it has been further suggested that, if anything, activation during phonation is right dominant in the gyral dLMC (Brown et al, 2020). In the present study, significant STRF tuning was observed only in the left dPM.…”
Section: Left Dpm: Encoding Of Vocal Pitch In the Dorsal Laryngeal Motor Cortexsupporting
confidence: 54%
“…Among primates, the dLMC is unique to humans and likely evolved to provide voluntary control of the larynx (Belyk & Brown, 2017;Dichter et al, 2018;Simonyan, 2014). It has been suggested that the dLMC contains sulcal (BA 4) and gyral (BA 6) components (Brown, Yuan, & Belyk, 2020). The seminal study by Brown and colleagues (2008) puts the left-hemisphere peak of the gyral component at MNI coordinate [-54, -2, 46] (see Figure 6, Discussion).…”
Section: Introductionmentioning
confidence: 98%
“…Among primates, the dLMC is unique to humans and likely evolved to provide voluntary control of the larynx (Belyk & Brown, 2017;Dichter et al, 2018;Simonyan, 2014). It has been suggested that the dLMC contains sulcal (BA 4) and gyral (BA 6) components (Brown, Yuan, & Belyk, 2020). The seminal study by Brown and colleagues (2008) puts the left-hemisphere peak of the gyral component at MNI coordinate [-54, -2, 46] (see Figure 7, Discussion).…”
Section: Introductionmentioning
confidence: 98%
“…Both LMC regions were involved during singing as well as whistling, suggesting their functional contribution to voicing and expiration. A different study from the same group tested the somatotopic representation of larynx and jaw muscles, demonstrating again a proximity in both pre-central sites ( Brown et al ., 2020 ), but no functional segregation.…”
Section: Introductionmentioning
confidence: 90%